ANALISIS LEARNING OBSTACLES DALAM PEMBELAJARAN MATERI PELUANG BESERTA PENERAPANNYA: SYSTEMATIC LITERATURE REVIEW - Riastuti, Ade (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to identify the learning barriers experienced by students with the opportunity to apply the material over the past few years. This research is based on qualitative research using the method of systematic literature review. Data collection techniques using data extraction. The criteria for data collection were carried out in several stages, namely: (1) collecting the same articles to study material opportunities; (2) identifying learning barriers in opportunity materials from articles obtained by researchers; (3) identifying the benefits or application of opportunity materials from articles obtained by researchers; and (4) compiling a report on the results of the analysis of student learning barriers in opportunity materials from articles obtained by researchers. Based on the research results from the analysis of 16 articles, it was identified that student learning obstacles in the opportunity material were grouped into three parts, namely: first, ontogenic obstacle, one of the triggers was lack of motivation to learn which had an impact on students who were enthusiastic in learning opportunity material; secondly epistemological constraints caused by students' intuitive responses or limitations in understanding the concepts of combinations and permutations of material opportunities; and the third is a didactic obstacle caused by limited sources of teaching materials, thus affecting the limited variety of questions and student experience in solving material opportunity problems. Opportunity material can also be applied in other disciplines such as education, health, finance, technology, and other fields.